PENGENDALIAN KUALITAS PRODUKSI LAKOP SAPU LANTAI DENGAN MENGGUNAKAN METODE SIX SIGMA DI UD. XY PURWOSARI - Latifah, Latifah; Rosyidi, Khafizh (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2018)
Control of production quality is a very important factor for the industrial world because good quality control and carried out continuously will be able to detect abnormalities of the process or production quickly, so that anticipatory action can be taken immediately. In general UD. Plastics which are SMEs engaged in printing. Has produced many products every year. But at every stage of the process, it is not free from the possibility of product damage. The company has reduced the defect product, but all types of damage must still occur. For this reason, quality control needs to be issued by the company. Damaged products fluctuate each month. Although the maintenance costs incurred by the company are quite large, the data above explains the total level of product defects that occur in UD. Plastic reached 32.21% of the production results. UD. Plastic Purwosari in April 2017 36800 seeds with a total defect of 448 seeds. Based on calculations, UD. Plastic Purwosari has a sigma level of 3.76 with a possible production yield defect of an average of 12918 for one million production (DPMO). After making repairs carried out in May 2017 using the Six Sigma method, it is known that the production yield of 35300 seeds with a total defect of 194 seeds. Based on the calculation of UD. Plastic Purwosari has increased with a sigma level of 4.04 with the possibility of defect of the average production of 5660 for one million production (DPMO).